RYZYKO ZACHOWAŃ KORUPCYJNYCH W INSTYTUCJACH PAŃSTWOWYCH NA PRZYKŁADZIE SŁUŻBY CELNEJ RP. ZAŁOŻENIA TEORETYCZNO-METODOLOGICZNE BADAŃ SOCJOLOGICZNYCH - Burzyński, Jan; Burzyński, Tomasz (Wydział Prawa i Administracji UAM, 2013)
Artykuł stanowi próbę nakreślania metodologii umożliwiającej socjologiczną konceptualizacją problemu ryzyka korupcji w instytucjach państwowych Rzeczpospolitej Polskiej. Proponowane podejście skupia się na pojęciu „zdarzenia korupcyjnego”, terminu łączącego w sobie podmiotowe predyspozycje do udziału w korupcyjnych wymianach wraz z ich systemowymi oraz strukturalnymi uwarunkowaniami. Dzięki obraniu teorii stawania się społeczeństwa, dokonano wglądu w zagadnienie korupcji z perspektywy tych teorii socjologicznych, które postulują ontologię rzeczywistości społecznej umożliwiającą przezwyciężenie dychotomii: podmiotowość – struktura społeczna.

***The paper is an attempt to outline a coherent methodological framework fostering a more sociologically informed perspective on the problem of corruption risk as it is typical of the functioning of state institutions in Poland. The approach is based upon the concept of a ‘corruption event’ which combines agential dispositions to take part in corrupt exchanges as well as their structural and systemic determinants. In this way, assuming the theory of social becoming as a starting point, the postulated methodology investigates the problem of corruption from the theoretical perspective of sociologies aiming to provide a holistic and synthetic ontology whose objective is to overcome the dichotomy between agency and structure.
RISK OF CORRUPTIVE BEHAVIOUR IN STATE INSTITUTIONS ON THE EXAMPLE OF THE CUSTOMS OFFICE IN POLAND: THEORETICAL AND METHODOLOGICAL ASSUMPTIONS OF SOCIOLOGICAL STUDIES
Keywords: korupcja; ryzyko; podmiotowość; determinacja strukturalna; corruption; risk; agency; structural determination